The Influence of Accountability and Human Resource Quality on Village Financial Management (A Study in the Villages of Biau District, North Gorontalo Regency) - Mii, Sri Panda; Blongkod, Harun; Dama, Hais (Nomico, 2024)
This study aims to determine the impact of accountability and human resource quality on village financial management in the villages of Biau District, North Gorontalo Regency. The study utilizes a quantitative methodology, collecting data through in-depth interviews and questionnaires. A total of 102 samples were used for this research. The study employs SEM AMOS, which stands for Structural Equation Analysis. The findings of this study indicate that accountability and human resource quality have a positive influence on village financial management in the villages of Biau District, North Gorontalo Regency. The theoretical framework used in this study is agency theory, which provides insights into the relationship between principals (those with interests) and agents (those who act on their behalf). The study concludes that accountability and human resource quality have a positive effect on village financial management in the villages of Biau District, North Gorontalo Regency.